Rekonstruksi Keamanan Maritim Indonesia Dalam Rangka Mewujudkan Ketahanan Wilayah (Studi Di Kabupaten Natuna Periode Tahun 2019-2020) - Panji Suwarno; Siswo Hadi Sumantri; Fauzi Bahar (Universitas Gadjah Mada, 2021)
ABSTRACT There were several things that were important points for Indonesia by paying attention to several things, firstly, Indonesia must be aware of the security situation in the North Natuna Sea, which was often disputed by several regional countries. Conflicts in regional areas would affect security because geographically, Indonesia was very close to this area and even directly in contact with the North Natuna Sea. The conflict would also have an impact on economic conditions, because the Natuna sea area was the crossing area of international ships that were going to industrial areas, including Indonesia. The purpose of this article was to analyzed the threats and reconstruct Indonesia's maritime security in the context of realizing national resilience. The case study of this research was on the Natuna sea conflict. This research used descriptive qualitative data analysis techniques. Based on the analysis, the threat analysis had been seen through response management against the form of violation in the Natuna sea area, by Bakamla RI, Lanal, Lantamal, and the Regional Government, also the Central Government through the Ministry of Foreign Affairs. This could be used as a form of development (reconstruction) for Indonesian Maritime Resilience in order to provided support for national resilience to strengthened national defense. ABSTRAK Terdapat beberapa hal yang menjadi poin penting bagi Indonesia dengan memperhatikan beberapa hal yaitu pertama, Indonesia harus mewaspadai situasi keamanan di Laut Natuna Utara yang sering terjadi sengketa oleh beberapa negara kawasan. Konflik di daerah kawasan akan mempengaruhi keamanan karena secara geografis wilayah Indonesia sangat berdekatan dengan wilayah tersebut dan bahkan bersinggungan langsung dengan wilayah Laut Natuna Utara. Konflik juga akan berimbas dengan kondisi ekonomi, dikarenakan wilayah laut Natuna merupakan perlintasan internasional kapal-kapal yang hendak berlayar menuju wilayah industrial termasuk Indonesia. Artikel ini bertujuan menganalisis ancaman dan rekontruksi kemanan maritim Indonesia dalam rangka mewujudkan ketahanan nasional.Studi kasus penelitian ini pada konflik perairan Natuna. Penelitian ini menggunakan teknik analisis data kualitatif deskriptif.Berdasarkan analisis, analisis ancaman sudah terlihat melalui manajemen respon terhadap bentuk pelanggaran di wilayah periaran Natuna, oleh Bakamla RI, Lanal, Lantamal dan Pemerintah Daerah, serta Pemerintah Pusat Melalui Kementerian Luar Negeri. Hal inilah yang dapat dijadikan sebagai bentuk bangunan (rekonstruksi) terhadap Ketahanan Maritim Indonesia guna memberikan dukungan terhadap ketahanan nasional untuk memperkuat pertahanan negara.